Continuous flow enteral feeding: first cases - Mate, Miguel; Prestinari, Elena; Carrera, Carlos; Sanguinetti, Julio; Servetti, Eduardo; Larre Borges, Uruguay (Cirugía del Uruguay, 1976)
On occasion of the presentation of three cases submitted to enteral feeding with continuous flow and low lischarge, the different methods of complementary feeding are revised and analyzed. The advantages and disadvantages of each of them are taken into consideration. The technique of enteral feeding by continuous flow is described. Clinical cases are discussed, and the method is accepted as satisfactory.